The essential writings of B.R. Ambedkar - Ambedkar, B. R. (Oxford University Press, 2002)
Providing an important introduction, this book is a compilation of judiciously selected, thoroughly edited writings of B. R. Ambedkar. It serves as an excellent guide to the evolution of his thought and should be a ready reference on Ambedkar's most important works for students and researchers of political science, history, and sociology. It will also interest all those who deal with scheduled castes, tribes, and social classes.